Dopant‐Free, Amorphous–Crystalline Heterophase SnO2 Electron Transport Bilayer Enables >20% Efficiency in Triple‐Cation Perovskite Solar Cells. (29th April 2020) - Lee, Hock Beng; Kumar, Neetesh; Ovhal, Manoj Mayaji; Kim, Yeong Jae; Song, Young Min; Kang, Jae‐Wook
Abstract: Improving the ohmic contact and interfacial morphology between an electron transport layer (ETL) and perovskite film is the key to boost the efficiency of planar perovskite solar cells (PSCs). In the current work, an amorphous–crystalline heterophase tin oxide bilayer (Bi‐SnO2 ) ETL is prepared via a low‐temperature solution process. Compared with the amorphous SnO2 sol–gel film (SG‐SnO2 ) or the crystalline SnO2 nanoparticle (NP‐SnO2 ) counterparts, the heterophase Bi‐SnO2 ETL exhibits improved surface morphology, considerably fewer oxygen defects, and better energy band alignment with the perovskite without sacrificing the optical transmittance. The best PSC device (active area ≈ 0.09 cm 2 ) based on a Bi‐SnO2 ETL is hysteresis‐less and achieves an outstanding power conversion efficiency of ≈20.39%, which is one of the highest efficiencies reported for SnO2 ‐triple cation perovskite system based on green antisolvent. More fascinatingly, large‐area PSCs (active areas of ≈3.55 cm 2 ) based on the Bi‐SnO2 ETL also achieves an extraordinarily high efficiency of ≈14.93% with negligible hysteresis. The improved device performance of the Bi‐SnO2 ‐based PSC arises predominantly from the improved ohmic contact and suppressed bimolecular recombination at the ETL/perovskite interface. The tailored morphology and energy band structure of the Bi‐SnO2 has enabled the scalable fabrication of highly efficient, hysteresis‐less PSCs. Abstract : The amorphous–crystalline heterophase SnO2 electron transport bilayer (Bi‐SnO2 ) exhibits improved surface morphology, fewer oxygen defects, and better energy band alignment with the perovskite, which enables more efficient electron extraction. The use of Bi‐SnO2 boosts the efficiency of small‐area (0.09 cm 2 ) and large‐area (3.55 cm 2 ) perovskite solar cells up to 20.39% and 14.93%, respectively.